Perkembangan Terkini Fotoproteksi: Analisis - Rezkyana Danil; Nelva Karmila Jufuf (PT Kalbe Farma Tbk., 2025)
Sunlight contains ultraviolet rays such as ultraviolet A (UVA) and ultraviolet B (UVB) rays have adverse effects on the skin such as photoaging, immunosuppression, photocarcinogenesis, and exacerbation of photodermatosis. Photoprotection is an important preventive measure. The use of sunscreen is an important and essential component; development of ultraviolet (UV) filters, sunscreens with topical antioxidants, and others, are current sunscreen innovations. However, sunscreens do not prevent visible light radiation hence the development of nontopical oral and subcutaneous photoprotection that has systemic effect. Development of physical photoprotection is by adjusting the type, color, and thickness of material. Other photoprotection is from ozone layer, weather, and selection of fabric or glass used as shades.